5x+2y-3z 3x-2y+2z=14 4x-2x-5z=9
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 20:30:22
5x+2y-3z3x-2y+2z=144x-2x-5z=95x+2y-3z3x-2y+2z=144x-2x-5z=95x+2y-3z3x-2y+2z=144x-2x-5z=9第一个不完整追问
5x+2y-3z 3x-2y+2z=14 4x-2x-5z=9
5x+2y-3z 3x-2y+2z=14 4x-2x-5z=9
5x+2y-3z 3x-2y+2z=14 4x-2x-5z=9
第一个不完整
追问
x/2=y/3=z/5 x+3y-z/x-3y+z
试证明(x+y-2z)+(y+z-2x)+(z+x-2y)=3(x+y-2z)(y+z-2x)(z+x-2y)
已知(x+y)(x+z)=x,(y+z)(y+x)=2y,(z+x)(z+y)=3z,求x,y,z
x+y+z=6 x+2y+3z=14 y+1=z
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..
3x+2y+z=14 ,x+y+z=10,z+2x+3y=1 5
已知2x+5y+4z=15.7x+y+3z=14 则x+y+z=?
三元一次方程组,1.x-2y+z=9 2x+y+3z=10 3x+2y1.x-2y+z=92x+y+3z=103x+2y-z2.3x-5y+2z=14x+5y-z=5X-5y+3z=-23.7x+2y-z=76x-y+z=74x+3y+z=94.4x+3y-2z=-75x-6y+z=12x+z=-25.2x+3y-4z=-23x-2y+5z=262x+5z=31
(4x-2y-z)-{5x-[8y-2z-(x-2y)]-x-(3y-10z)}=?
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
证明 :x/(y+z)+y/(z+x)+z/(x+y)>=3/2其中 x,y,z>0
x+2y=3x+2z=4y+z 求x:y:z
x+y/2=z+x/3=y+z/4 x+y+z=27
若x+y+z=3y=2z,则x/x+y+z=?
{x+y+z=1;x+3y+7z=-1;z+5y+8z=-2
x+2y+3z=23 y-z=5 x+2z=10
设|x|-|y|+|z|=|x+y+z|,且|x+y|=4,|y+z|=5,|y|=3,求(x-y-z)^2的值
已知x/y+z=y/x+z=z/x+y,分式(x+2y+3z)/(2x+5y-2c)有意义时的值